Relation of poverty with treatment-seeking behavior and antibiotic misuse among UTI patients in Pakistan - Hussain, Iltaf; Shukar, Sundus; Subhan Arshad, Muhammad; Rasool, Muhammad Fawad; Chang, Jie; Fang, Yu (Frontiers in Public Health, 2024)
The current study aimed to assess the relation of multi-dimension poverty with treatment-seeking behavior and antibiotic misuse, among urinary tract infection (UTI) patients.A cross-sectional approach was utilized to recruit patients who had a history of UTI in the previous month from two provinces of Pakistan. The treatment-seeking behavior and antibiotic misuse data were collected on a selfdeveloped questionnaire, whereas the poverty data was collected on a modified multi-dimension poverty index (MPI). Descriptive statistics was applied to summarize the data. The logistic regression analysis was carried out to assess the association of multi-dimension poverty with patient treatment-seeking behavior and antibiotic misuse.A total of 461 participants who had UTI symptoms in the previous month were recruited. Most of the participants in the severely deprived stage, treated the UTI (p<0.001), however, there was a high proportion of the participants who consulted with friends and family for UTI treatment (p<0.001). The patients in the deprivation status (deprived and severely deprived) were less associated with formal consultation. The poorer subgroups were less likely to practice antibiotic course completion.The current study highlighted that poverty has an important role in antibiotic misuse. Poorer subgroups were associated with informal consultations and incompletion of the antibiotic course. Further studies are needed to explore the potential role of poverty in treatment-seeking behavior and antibiotic misuse.